Forms of Linguistic Deviations Found in Latah Coprolalia Behavior in Jombang, East Java, Indonesia - Sri Pamungkas (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
Latah is a psychogenic language disorder in Malay and Indonesian society stemming from cultural pressure, mimicry, and the like. It is expressed as a verbal or nonverbal response to surprise or shock. The focus of this research was the form of linguistic deviation in individuals in Jombang, East Java, with latah coprolalia behavior, specifically latah behavior by expressing lingual forms that refer to the male or female genitalia. Data collection comprised observations and interviews, while data analysis used Spardley’s ethnographic approach with four advanced paths: (1) domain analysis, (2) taxonomy analysis, (3) componential analysis, and (4) culture values analysis. The findings showed that latah coprolalia behavior occurs in men with both low and high education levels, and women with low education levels, but is not found in women with high education levels. Patting and verbal stimuli give rise to syntagmatic errors in the form of single words and sentences in men with high education, while in men with low education, syntagmatic errors happen in single sentences and multiple sentences. Meanwhile, women with low educational backgrounds displaying latah coprolalia behavior were identified as committing syntagmatic errors in the form of single words and sentences.